The Power of Narrative (KULT_online, 2009)
Stories were instrumental in legitimising imperial expansion – this is how Edward Said described the role of narrative, specifically that of the novel, in his now classic study Culture and Imperialism (1993). Closely corresponding to the narrative turn in literary and cultural studies, this discussion of the connection between story and empire is continued in a recent collection of articles, which utilises cognitive approaches to narrative and contributes new insights into how profoundly the experience of empire has been shaped by narrative structures. Thus, not only novels are taken into view, but also the fine and deep structures of narrative which extend right to the sphere of cognitive schemata and scripts.